Risk factors of mandibular angle fractures based on digital reduction method: a retrospective analysis - Dilek ŞAHAR; Aydın Onur GERÇEK; Nuray BAYRAKÇI (BMC Oral Health)
Abstract Aim This study aimed to evaluate radiomorphometric risk factors for mandibular angle fractures (MAFs) by simulating pre-fracture mandibular anatomy using digital reduction techniques on cone beam computed tomography (CBCT) images. Demographic and etiological characteristics were also analyzed to identify factors associated with MAF occurrence. Methods In this retrospective study, 55 patients with mandibular fractures were categorized into two groups: those with mandibular angle fractures (MAF, n = 20) and those with fractures in other mandibular regions (non-MAF, n = 35). High-resolution CBCT scans were analyzed following digital fragment realignment using Materialise Mimics 25.0. Radiomorphometric measurements included gonial angle, ramus height, and ramus width. Demographic variables, third molar status, and trauma etiology were evaluated. Statistical analysis was performed using Mann–Whitney U, chi-square, Fisher’s exact, and independent samples t tests, with a significance level of p < 0.05. Results Patients in the MAF group were significantly younger (median age: 21 vs. 27 years; p = 0.002) and predominantly male (90%). Third molars were more frequently observed in the MAF group (85%) and were significantly associated with angle fractures (p = 0.019). Condylar fractures occurred in 42.9% of the non-MAF group but were absent in the MAF group (p < 0.001). Conclusion CBCT combined with digital reduction improves anatomical assessment and standardization in fracture evaluation. Younger age, male gender, and the presence of third molars were significantly associated with MAFs. Third molars may represent a modifiable risk factor for mandibular angle fractures and should be considered carefully in clinical prevention strategies.